2008
DOI: 10.1002/pat.1045
|View full text |Cite
|
Sign up to set email alerts
|

Dye removal by a novel hydrogel‐clay nanocomposite with enhanced swelling properties

Abstract: Acrylamide (AAm)‐2‐acrylamide‐2‐methylpropanesulfonic acid sodium salt (AMPSNa) hydrogel and AAm‐AMPSNa/clay hydrogel nanocomposite having 10 w% clay was prepared by in situ copolymerization in aqueous solution in the presence of a crosslinking agent (N,N′‐methylenebisacrylamide (NMBA)). Swelling properties and kinetics of the hydrogel samples were investigated in water and aqueous solutions of the Safranine‐T (ST) and Brilliant Cresyl Blue (BCB) dyes. The swelling and diffusion parameters were also calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…For Fickian diffusion mechanism n is 0 B 0.5, for non-Fickian or anomalous diffusion, n is between 0.5 and 1.0. Also, n is 1.0 for the Case II diffusion (relaxation-controlled transport) and for the supercase II diffusion, n is greater than 1.0 [24]. A plot of ln(W t /W ? )…”
Section: Mechanism Of Water Uptake and Diffusion Coefficientmentioning
confidence: 98%
“…For Fickian diffusion mechanism n is 0 B 0.5, for non-Fickian or anomalous diffusion, n is between 0.5 and 1.0. Also, n is 1.0 for the Case II diffusion (relaxation-controlled transport) and for the supercase II diffusion, n is greater than 1.0 [24]. A plot of ln(W t /W ? )…”
Section: Mechanism Of Water Uptake and Diffusion Coefficientmentioning
confidence: 98%
“…sponge, cotton, wood pulp and colloidal silica, etc. ), superabsorbents have been extensively applied in many fields such as hygienic products (Kosemund et al, 2009), agriculture (Doane & Doane, 2005;Liang, Yuan, Xi, & Zhou, 2009;Puoci et al, 2008) wastewater treatment (Kaş göz & Durmus, 2008;Kaş göz, Durmuş , & Kaş göz, 2008;Wang, Zhang, & Wang, 2008) and drug-delivery systems (Sadeghi & Hosseinzadeh, 2008;Wang, Zhang & Wang, 2009), etc. However, there are limitations to such applications because most of superabsorbents used as disposable particles are based on fully petroleum-based polymers with high production cost and serious environment impact (Kiatkamjornwong, Mongkolsawat, & Sonsuk, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are widely used in agriculture, horticulture, hygienic products, drugdelivery systems and effluent treatment. [7][8][9][10] Clay minerals with layered structures such as montmorillonite, kaolin, attapulgite, mica and vermiculite, have been used to prepare superabsorbent composites. Su et al 11 prepared MMT/PAA superabsorbent composite and found that incorporation of MMT into PAA could improve the water absorbency, swelling ability and thermal stability of products.…”
Section: Introductionmentioning
confidence: 99%